Immunohistochemical detection of 1,N6-ethenodeoxyadenosine in nuclei of human liver affected by diseases predisposing to hepato-carcinogenesis - Frank, Alexander P.; Seitz, Helmut K.; Bartsch, Helmut; Frank, Norbert; Nair, Jagadeesan (Carcinogenesis, 2004)
Increased oxidative stress and lipid peroxidation (LPO) are implicated in multistage carcinogenesis. Recent studies have shown that LPO-derived reactive hydroxyalkenals can form promutagenic exocyclic etheno-DNA adducts in vivo . Such DNA damage was found to be increased in the liver of patients with metal storage diseases and in colon adenomas of familial adenomatous polyposis patients. We now have investigated the levels of 1, N6 -ethenodeoxyadenosine (εdA) in human liver samples obtained from a group of patients diagnosed with hepatitis, fatty liver, fibrosis and cirrhosis, primary hemochromatosis and Wilson's disease. Using an immunohistochemical method, the relative mean pixel intensity of randomly selected nuclei was measured by imaging software; positively stained cell nuclei (arbitrary mean pixel intensity ≥0.5) were counted. Prevalence of εdA (%) was calculated from the ratio of a number of positively stained cell nuclei over a total number of cells counted. When compared with normal livers (3.1%), the percent prevalence (means) was significantly higher in specimens of alcoholic fatty liver (15%) and fibrosis patients (50%) but not in samples with hepatitis (induced by various factors) (6.2%). The percent prevalence in alcohol fibrosis was as high as in the liver from Wilson's disease (50.7%) and hemochromatosis (33%) patients. This is the first demonstration of increased εdA in human liver diseases due to alcohol abuse. We conclude that excessive hepatic DNA damage, as assessed by miscoding etheno-DNA adduct in the nuclei of liver biopsies, is probably caused by alcohol-induced oxidative stress and LPO. In cancer-prone liver diseases (fatty liver, cirrhosis/fibrosis) such damage may act as a driving force towards malignancy.